Encapsulation of Monascus Pigments Using Enzyme-Modified Yeast Protein–Polysaccharide Complex Pickering Emulsions to Increase Its Stability During Storage - Ziyan Zhao; Jinling Zhao; Sirong Liu; Mengxuan Liu; Xiangquan Zeng; He Li; Yu Xi; Jian Li (Foods)
Yeast protein (YP) is rich in nutrients, but its emulsifying properties, especially emulsifying stability, still need to be improved. In this study, cationic polysaccharide chitosan (CS) and anionic polysaccharide xanthan gum (XG) were selected to enhance the emulsifying properties of protein emulsions. The preparation conditions of the emulsions were optimized by calculating particle size, zeta potential, emulsifying activity index, emulsifying stability index, and emulsifying capacity index, as well as macroscopic observation. The optimized emulsions were characterized using confocal laser scanning microscopy, rheology, Raman spectroscopy, color difference analysis, and storage stability. The results showed that the stability of yeast protein/modified yeast protein–chitosan (YP/EYP–CS) emulsions was better at pH 5.5, with a protein:polysaccharide ratio of 1:1 and an oil phase addition of 40%, while the stability of yeast protein/modified yeast protein–xanthan gum (YP/EYP–XG) emulsions was better at pH 3.5, with a protein:polysaccharide ratio of 1:1 and an oil phase addition of 50%. Further analysis indicated that the emulsions with CS had smaller particle sizes and lower initial viscosities, but more hydrogen bonds and better encapsulation of Monascus pigment (MP), especially the EYP–CS emulsion (81.18%). In contrast, the emulsions with XG had uniform droplet sizes and high thermal stability and exhibited obvious shear thinning behavior with increasing shear rates. The network structure of the emulsions was mainly elastic, and the hydrophobic interaction was stronger. This study provides insights into the utilization of yeast protein in the food industry and the development of emulsification systems.